Respuesta :

Answer:

Simplifying

5[x + -4] + 4 + r = 4[x + 3] + x

Reorder the terms:

5[-4 + x] + 4 + r = 4[x + 3] + x

[-4 * 5 + x * 5] + 4 + r = 4[x + 3] + x

[-20 + 5x] + 4 + r = 4[x + 3] + x

Reorder the terms:

-20 + 4 + r + 5x = 4[x + 3] + x

Combine like terms: -20 + 4 = -16

-16 + r + 5x = 4[x + 3] + x

Reorder the terms:

-16 + r + 5x = 4[3 + x] + x

-16 + r + 5x = [3 * 4 + x * 4] + x

-16 + r + 5x = [12 + 4x] + x

Combine like terms: 4x + x = 5x

-16 + r + 5x = 12 + 5x

Add '-5x' to each side of the equation.

-16 + r + 5x + -5x = 12 + 5x + -5x

Combine like terms: 5x + -5x = 0

-16 + r + 0 = 12 + 5x + -5x

-16 + r = 12 + 5x + -5x

Combine like terms: 5x + -5x = 0

-16 + r = 12 + 0

-16 + r = 12

Solving

-16 + r = 12

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '16' to each side of the equation.

-16 + 16 + r = 12 + 16

Combine like terms: -16 + 16 = 0

0 + r = 12 + 16

r = 12 + 16

Combine like terms: 12 + 16 = 28

r = 28

Simplifying

r = 28